I, Maya Plisetskaya - Pliset͡skai͡a, Maĭi͡a, 1925-2015 (Yale University Press, 2001)
Maya Plisetskaya rose to become a prima ballerina of Moscow's Bolshoi Ballet after an early life filled with tragedy. Here Plisetskaya reflects on her personal and professional odyssey presenting the life of a Soviet artist from the 1930s to 1990s.